2017
DOI: 10.5455/ajvs.259376
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chitosan Gel on Wound Healing: Experimental Study in Donkeys

Abstract: Key words:Chitosan gel, Donkeys, Histopathological changes, Wound healing Chitosan is one of the natural bioactive materials known for its wound healing effect. Healing of equine's wounds are often delayed and complicated. This study aimed to evaluate efficacy of chitosan gel on healing of equine skin-wounds in comparison to povidone-iodine (as control). Six adult male donkeys were used and divided equally into two groups; group A (2x2 cm skin-wound) and group B (4x4 cm skin-wound). Full thickness skin-wounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…The use of a CDHP dressing on full-thickness wounds with cavities was supported by previous studies. 2 10 28 29 30 31 This dressing can keep the wound moist and enhance granulation tissue. This clinical trial demonstrated the effectiveness of CDHP dressings in wound bed preparation concerning granulation and removal of necrotic tissue from cavitation wounds.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a CDHP dressing on full-thickness wounds with cavities was supported by previous studies. 2 10 28 29 30 31 This dressing can keep the wound moist and enhance granulation tissue. This clinical trial demonstrated the effectiveness of CDHP dressings in wound bed preparation concerning granulation and removal of necrotic tissue from cavitation wounds.…”
Section: Discussionmentioning
confidence: 99%
“…40 The Chitin demineralization process from biomass (chicken feet) was carried out by Morganti et al, 41 using 1: 18 (w/v) at 1.5 M solutions of Hcl for 36 h at room temperature. 42 While it claimed that 97% demineralization was achieved, another report by Cao, 40 stated that the demineralization efficiency was 99% when a 0.55 M solution of Hcl was used in the ratio of 1:10 (w/v) to dissolve crab shells in 15 min at room temperature. In the same study, it was found that substituting crab shells with cuttlefish shells resulted in a demineralization value of 98%, with all other parameters and concentrations unchanged.…”
Section: Chemical Demineralization Methods For Chitin Extractionmentioning
confidence: 99%
“…The width and the length of wounds were measured using digital caliber after the wound had been carefully cleaned by saline to visualize wound margins. The wound surface area, percentage of wound size, and wound contraction percent were calculated using the following equations (Zaid et al, 2017).…”
Section: Estimation Of Wound Healing Clinical Evaluation Of the Woundsmentioning
confidence: 99%